Evaluating Research on Natural Resource Management: The Case of Soil Fertility Management in Kenya - Omamo, Steven Were; Kilambya, Daniel W.; Nandwa, S. (International Service for National Agricultural Research, 1999)
A fundamental challenge facing Kenya's agricultural research establishment is how to demonstrate that new initiatives in research on soil fertility management can contribute to national growth and equity objectives. A simplified method for quantifying the value of research in soil fertility management has been developed through a collaborative effort made by ISNAR and KARI, the Kenya Agricultural Research Institute. This method estimates the possible economic benefits that could ultimately result from research-induced increases in commodity yields. The results suggest that efforts to integrate applied commodity-focused research with farming-systems-oriented adaptive research initiatives are important. They also indicate that, while high rainfall areas will experience the largest gains on aggregate, significant benefits also accrue to Kenya's arid and semi-arid areas. However, the method is not yet fully satisfactory. Certain limits on data and resources prevented the procedure from allowing for variations due to differences in estimated net yield gains. Differences in impact were instead attributed to variations in the quantities of specific commodities produced per zone. Potential benefits that are unrelated to commodity yields are also ignored.